Quantitative assessment of vaginal microflora during use of tampons of various compositions. - Onderdonk, A B (1987)
Although the effect of vaginal tampons on the microbial flora during menstruation has recently been studied by several investigators, quantitative effects attributable to particular tampon fibers have received less attention. The purposes of the present study were (i) to determine and then to compare the effects of polyacrylate rayon tampons and viscose rayon tampons on the normal vaginal flora, (ii) to compare quantitative bacterial counts obtained from these tampons with those obtained from concomitant vaginal swabs, and (iii) to determine whether either of these tampon types alters the vaginal microflora when compared with the microflora in the same women using all-cotton tampons or external catamenial pads. Tampon and swab samples were obtained at predetermined times from 18 women for an average of seven menstrual cycles. Samples consisting of swabs from women wearing menstrual pads were compared with swab and tampon samples taken at predetermined times during the menstrual cycle from women using cotton, polyacrylate rayon, or viscose rayon tampons. Samples were analyzed for total aerobic, facultative, and anaerobic bacterial counts. Statistical evaluation of the results indicated that, on the whole, total bacterial counts decreased during menstruation and that the numbers of bacteria in tampons tended to be lower than those in swab samples taken at the same time. The tampon type had little effect on the vaginal microflora.